Customer Satisfaction: Mediating Customer Loyalty in Foodservice Industry Dynamics: Dinamika Loyalitas Pelanggan: Peran Mediasi Kepuasan Pelanggan di Industri Layanan Makanan - Evi Widianti; Mudji Astuti (Academia Open, 2023)
This quantitative research study investigates the influence of price, service quality, and sales location on customer loyalty, with customer satisfaction acting as the mediating variable. Utilizing a purposive sampling method, data were collected from 99 respondents at Café Lare Darjo. Path analysis, employing Smart-PLS version 3.0 software, was employed for data analysis. The findings reveal intricate relationships between the variables, highlighting that customer satisfaction mediates the effects of price, service quality, and sales location on customer loyalty. These results have significant implications for both academia and practitioners in the global foodservice industry, offering valuable insights and a framework to enhance customer loyalty through targeted improvements in pricing, service quality, and sales location strategies. Highlights: Customer satisfaction plays a crucial role as a mediating variable in the relationship between price, service quality, sales location, and customer loyalty. This study utilizes a quantitative approach and path analysis to explore the intricate relationships between variables. These findings provide valuable insights for both academics and practitioners in the global food service industry, offering a framework for enhancing customer loyalty through targeted improvements in price, service quality, and sales location strategies. Kata Kunci : Customer Loyalty, Price, Service Quality, Sales Location, Customer Satisfaction.